A Qualitative Study of the Day-to-Day Lives of Families of Indian Squatters in Desa Mentari Hardcore Poor Housing Scheme in Taman Medan, Selangor - Michael, Edwin; Eng , May Chuen; Teh , Boon Teck (School of Social Sciences, 2015)
This study focuses on the impact of migration of Kampung Gandhi and Kampung Medan squatter residents to Desa Mentari Hardcore Poor Housing scheme in Taman Medan. This study also examined the factors behind the continued resurfacing of urban poverty among the squatter residents and the impact towards their daily lives in a city. To achieve the study’s objectives a qualitative methodological approach was adopted which included the use of intensive interviews. Finding shows that a number of challenges are being faced by the squatter residents ranging from poor sanitation services to the challenge of social vices in Desa Mentari flats. Furthermore, findings also shows that a number of factors ranging from escaping high living costs, increasing family sizes and escaping the impacts of urban poverty were some of the factors that are behing the continued social ill problems resurfacing among the squatter residents in Desa Mentari Hardcore Poor Housing in Taman Medan.